DISTRIBUTION ANALYSIS OF CLEAN WATER QUALITY USING HYDROPHYSICAL DATA IN MARSELA VILLAGE, MASELA ISLAND DISTRICT, SOUTHWEST MALUKU REGENCY, MALUKU PROVINCE - Souisa, Matheus; Sapulete, Sisca M.; Waimalaka, Raras F. (Universitas Mataram, 2023)
In situ measurements of hydrophysical parameters have been carried out in groundwater in dug wells, drilled wells, and reservoirs related to temperature, electrical conductivity, degree of acidity, salinity, and total dissolved solids (TDS). This study aims to analyze the characteristics of hydrophysical parameters in water samples and create a water quality distribution model based on hydrophysical data in the study area. The results showed that water zoning based on air temperature and water temperature is included in the mesothermal zone category, and this zone water may originate from free/leaking aquifers. The results of hydrophysical parameter measurements were TDS with a concentration value of < 1000 mg/L, conductivity parameter (s) with a concentration value of s < 2500 mS/cm, a pH parameter ranging from 7, and a salinity parameter with a concentration value < 1000 ppm which is allowed according to water quality standards which are found in dug wells (old wells, SGM-3), drilled wells (SBM) and pond (Em). While the hydrophysical parameters for measuring other groundwater samples are not in accordance with water quality standards. Modeling the distribution of water quality based on three hydrophysical parameters (TDS, s, and S) in the study area shows a shallow groundwater pattern and seawater intrusion has occurred in several wells (SGM-1, SGM-2, and SGM-4). The distribution of TDS, s, and S concentration values at study sites varies with distance from the coastline and topography.